Pemberian Bahan Amandemen untuk Perbaikan Retensi Hara Tanaman Jeruk Manis (Citrus sinensis L.) di Desa Talimbaru Kecamatan Barusjahe Kabupaten Karo - Rina Indriany P Pakpahan; Sarifuddin Sarifuddin; Supriadi Supriadi (Universitas Sumatera Utara, 2016)
This study aimed to determine the diverification of the amendment to the base saturation and production of sweet orange. This research was conducted in plantation citrus Talimbaru Village Barusjahe District Regency of Karo with plant age of ± five years and soil analysis at the Laboratory of PT. Socfin Indonesia and Laboratory Research and Technology Faculty of Agriculture, University of North Sumatra. This experiment using a Nonfaktorial Randomized Block Design (RAK) which consists of 5 treatments, namely B0 = Without Amendment (control), BP1 = Cow Manure (8,07 kg/plant), BP2 = Chicken Manure (8.15 kg/plant) , BA1 = Powder Ash (8,11 kg/plant), and BA2 = Shells Palm Oil (8.15 kg/plant) three replications. This research was conducted for 4 months. The parameters were measured soil pH, organic-C, P-available, N-total, CEC, K-exchange, Ca-exchange, Mg-exchange, Na-exchange, base saturation, and production citrus. The results showed that application of amendment materials palm shells and cow manure can improve base saturation so that citrus fruits production increased. Cow manure amendment supply bases Ca and Mg while shells palm oil supply base K in the soil. All amendment increased pH and soil organic C.Keywords : Cow Manure, Chicken Manure, Powder Ash, Shells Palm Oil, Nutrient Retention, CitrusThis study aimed to determine the diverification of the amendment to the base saturation and production of sweet orange. This research was conducted in plantation citrus Talimbaru Village Barusjahe District Regency of Karo with plant age of ± five years and soil analysis at the Laboratory of PT. Socfin Indonesia and Laboratory Research and Technology Faculty of Agriculture, University of North Sumatra. This experiment using a Nonfaktorial Randomized Block Design (RAK) which consists of 5 treatments, namely B0 = Without Amendment (control), BP1 = Cow Manure (8,07 kg/plant), BP2 = Chicken Manure (8.15 kg/plant) , BA1 = Powder Ash (8,11 kg/plant), and BA2 = Shells Palm Oil (8.15 kg/plant) three replications. This research was conducted for 4 months. The parameters were measured soil pH, organic-C, P-available, N-total, CEC, K-exchange, Ca-exchange, Mg-exchange, Na-exchange, base saturation, and production citrus. The results showed that application of amendment materials palm shells and cow manure can improve base saturation so that citrus fruits production increased. Cow manure amendment supply bases Ca and Mg while shells palm oil supply base K in the soil. All amendment increased pH and soil organic C.Keywords : Cow Manure, Chicken Manure, Powder Ash, Shells Palm Oil, Nutrient Retention, Citrus